Acellular cartilage matrix biomimetic scaffold with immediate enrichment of autologous bone marrow mononuclear cells to repair articular cartilage defects. (June 2022) - Jia, Litao; Zhang, Peiling; Ci, Zheng; Hao, Xiaoyan; Bai, Baoshuai; Zhang, Wei; Jiang, Haiyue; Zhou, Guangdong
Abstract: Functional repair of articular cartilage defects is always a great challenge in joint surgery clinically. Tissue engineering strategies that combine autologous cell implantation with three-dimensional scaffolds have proven effective for repairing articular cartilage tissue. However, it faces the problem of cell sources and scaffold materials. Autologous chondrocytes and bone marrow are difficult to popularize clinically due to limited donor sources and low mononuclear cell (MNC) concentrations, respectively. The density gradient centrifugation method can increase the concentration of MNCs in fresh bone marrow by nearly a hundredfold and achieve immediate enrichment. In addition, acellular cartilage matrix (ACM), with good biocompatibility and a cartilage-specific microenvironment, is considered to be an ideal candidate scaffold for cartilage regeneration. In this study, hybrid pigs were used to establish articular cartilage defect models of different sizes to determine the feasibility and maximum scope of application of ACM-based biomimetic scaffolds combined with MNCs for inducing articular cartilage regeneration. Importantly, ACM-based biomimetic scaffolds instantly enriched MNCs could improve the repair effect of articular cartilage defects in situ, which established a new model of articular cartilage regeneration that could be applied immediately and suited for large-scale clinical promotion. The current study significantly improves the repair effect of articular cartilage defects, which provides scientific evidence and detailed insights for future clinical applications of ACM-based biomimetic scaffolds combined with MNCs. Graphical abstract: Image 1 Highlights: Explore the maximum scope of repairing articular cartilage defect with ACM scaffold. Immediate enrichment of mononuclear cells by density gradient centrifugation. ACM scaffold enriched MNCs improve the repair effect of articular cartilage defect. Enrichment of MNCs expands the maximum scope of repairing articular cartilage defect.